Prevalence of Diabetes Mellitus (DM) in a population of men affected by Erectile Dysfunction (ED) - Mazzilli, R; Elia, J; Delfino, M; Benedetti, F; Scordovillo, G; Mazzilli, F (Clinica terapeutica, 2015)
A) to evaluate the prevalence of patients affected by Diabetes Mellitus (DM) in a population of men with Erectile Dysfunction (ED); B) to define the epidemiological, biochemical and therapeutic aspects. N.934 subjects referred at our Andrology Unit for ED were studied. The diagnosis of ED was evaluated using the IIEF-5 questionnaire (Total score ≤21). The prevalence of subjects affected by DM in a population of men with ED was 19.5% (182/934). The age ranges were: ≥55 years (108/182; 59.3%); ≥40<55 years (70/182; 38.5%); <40 years (4/182; 2.2%). HbA1c mean value was 7.9% ± 0.8%. No significant differences were found in DM onset timing or in anti-diabetic treatment. In n.125/182 cases (68.7%) the ED onset followed the diagnosis of DM; in n.34/182 cases (18.7%) it appeared at the same time; and in n.23/182 cases (12.6%) appeared before DM diagnosis. in n.18/182 subjects (9.9%) there was a concomitant hypotestosteronemia; these patients were treated only with testosterone replacement; this treatment was efficacious (IIEF-5 total score ≥22) in 8/18 subjects (44.4%). In n.146/182 subjects (80.2%) a treatment with PDE5-i was given. Of these 146 subjects, the therapy was given "on demand" to 108 subjects (efficacy in 50.9%; 55/108) and "once a day" to the remaining 38 subjects (efficacy 63.1%, 24/38) (p=0.428, n.s.). N.15/182 subjects (8.2%) were treated with intracavernous injections of Alprostadil (efficacy in 8/15, 53.3%). In n.3/182 subjects (1.6%) a penile prosthesis was implanted. DM is one of the most frequent organic causes of ED; there were many strategies to treat this symptom without interfering with the antidiabetic treatment. Finally, ED can be predictive of DM.